PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA PEGAWAI PUSKESMAS PADA KECAMATAN TAMBUN SELATAN - Gerry Adam Mustofa; Nelly Martini (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
His study aims to determine and analyze the partial or simultaneous effect of motivation and discipline on the performance of Public Health Center employees in South Tambun District. This type of research is a type of quantitative research with descriptive verification research methods. Samples of Puskesmas employees in South Tambun sub-district were taken 145 employees. The sampling technique in this study used the saturated sample technique. The analytical tool used in this study uses SPSS 22 software for windows. The analysis model in this study uses a path analysis model. Based on the results of the study, it showed that there was a partial effect of motivation on the performance of Puskesmas employees in Tambun Selatan District of 27.5%. While the partial effect of Discipline on the Performance of Public Health Center Employees in Tambun Selatan District is 25.4%. The simultaneous influence of motivation and discipline on employee performance is 86.7%. The influence of other variables outside the model is 13.3%.